Robust computational approach to determine the safe mud weight window using well-log data from a large gas reservoir; Marine and Petroleum Geology; Vol. 142 - Beheshtian S. Saeed; Rajabi M. Meysam; Davoodi Sh. Shadfar; Wood D. A. David; Ghorbani H. Hamzeh; Mohamadian N. Nima; Ahmadi A. M. Alvar Mehdi; Band Sh. S. Shahab (2022, 2022)
Title screen